An electron transport material phenanthroline derivative and its synthesis and application method

By optimizing the synthesis method of phenanthrene derivatives, improving its glass transition temperature and electron mobility, the shortcomings of existing electron transport materials in these aspects are solved, and efficient electron conduction performance and suitable for large-scale production are achieved.

CN116606296BActive Publication Date: 2025-03-04西安欧得光电材料有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310618040.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-30
Publication Date
2025-03-04
Estimated Expiration
2043-05-30

AI Technical Summary

Technical Problem

Existing electron transport materials have shortcomings in electron mobility and glass transition temperature (Tg), and the synthesis process is inconvenient and difficult to mass production on a large scale.

Method used

A synthesis method of phenanthrene derivative is adopted to improve the Tg and electron mobility of the material through specific reaction steps and conditions, and optimize the group structure to enhance the electron injection performance and hole blocking ability of the material.

Benefits of technology

The Tg value of the material is significantly improved, making it between 148°C and 203°C, enhancing electron conduction performance, improving the energy level of HOMO and LUMO, and the synthesis process is relatively simple, suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116606296B_ABST
    Figure CN116606296B_ABST
Patent Text Reader

Abstract

The present invention discloses an electron transport material, a phenanthroline derivative, and a synthesis and application method thereof. The phenanthroline compound is further fused to significantly increase the Tg of the material. The Tg values ​​of compounds 1 to 9 are distributed between 148° C. and 203° C., which are all very high Tg values ​​and fully meet the conventional use temperature requirements. The present invention also increases the large conjugated π bond inside the molecule, effectively improving the electron affinity of the molecule itself. The present invention performs N atom hybridization replacement on the C atom on the phenanthroline, thereby enhancing the electron accepting site of the molecule itself, and making the material have excellent electron binding ability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of organic chemical synthesis, and in particular relates to an electron transport material phenanthroline derivative and a synthesis and application method thereof. Background Art

[0002] In order to significantly improve the luminous efficiency of OLED devices, OLED devices currently use a multi-layer composite configuration, and achieve a greater improvement in luminous efficiency through the organic combination of various functional layers. In addition to improving the luminous efficiency of the luminescent material itself, improving the conduction efficiency of electrons and holes in the luminescence process can also greatly improve the luminous efficiency of the luminescent device.

[0003] In comparison of the efficiency of hole conduction and electron conduction in most organic materials currently developed, the hole conduction efficiency is much greater than the electron conduction efficiency. Therefore, it is very urgent to develop electron conduction materials with equivalent hole conduction efficiency to the current ones.

[0004] At present, mature OLED devices have achieved a good electron injection process in the cathode through organic doping or combination of alkali metal or alkaline earth metal oxides, fluorides, etc. However, the electron conduction material for conducting electrons from the electron injection layer to the light-emitting layer is relatively small, and the efficiency is not ideal.

[0005] There are seven major categories of electron transport materials currently developed, namely: oxazole derivatives or other azole compounds, metal chelates, azaanthracene derivatives, quinoline derivatives, perfluorooligomers, and diazine phenanthroline derivatives.

[0006] Among them, oxazole derivatives were used the earliest and have been widely studied. However, due to the relatively less intramolecular conjugation of small molecule oxazole derivatives, their glass transition temperature (Tg) is low during use, which affects the life of the device. In order to improve Tg, people mix their derivatives with polymer coating materials, but they are easily separated from the polymer materials and the actual use effect is not good. In addition, oxazoles are designed into dendrimers to improve the above shortcomings, but this type of compound has good solubility and is difficult to purify in the actual synthesis process, so its application and promotion are seldom.

[0007] Metal chelate transport materials have relatively weak chemical bonds, and in actual use, the stability of the chelate is often broken, resulting in a decline in overall component performance. There are few compounds like Alq3 that have been promoted for application.

[0008] Azaanthracene and quinoline derivatives are less widely used because of their difficulty in synthesis due to the limited number of cyclization methods.

[0009] Although perfluorooligomers have excellent electron transport capabilities, they are almost insoluble in any organic solvents and are highly crystalline, which brings huge resistance in the actual synthesis process and limits their promotion and use.

[0010] Phenanthroline derivatives have a higher electron transfer rate and suitable LUMO and HOMO energy levels, but currently small molecular weight phenanthroline derivatives (such as 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline) are limited in practical application due to their lower Tg.

[0011] The disadvantages of the prior art are mainly: low electron mobility, low Tg, inconvenient synthesis, and difficult purification and preparation.

[0012] In view of the general direction of current electron transport materials and the characteristics of the materials themselves, combined with the actual development process of current OLED materials, it is necessary to develop new materials with high electron mobility, high Tg glass transition temperature, convenient synthesis process, large-scale mass production and easy purification and preparation. Summary of the invention

[0013] The purpose of the present invention is to overcome the deficiencies of the prior art and provide an electron transport material, a phenanthroline derivative, and a method for synthesizing and applying the same.

[0014] In order to solve the technical problem, the technical solution of the present invention is: a method for synthesizing a phenanthroline derivative of an electron transport material, comprising the following steps:

[0015] Step 1: Substrate A and substrate B react to generate intermediate C. The molar ratio of substrate A to substrate B is 1:1 to 1.1. The structural formula of substrate A is The structural formula of substrate B is The structural formula of intermediate C is Wherein R2 is a phenyl group substituted with an alkyl group or a cycloalkyl group, and R5 is a fluorine, chlorine, bromine or a benzazaheterocyclic substituent group introduced by reaction;

[0016] Step 2: Intermediate C and benzamidine hydrochloride undergo dehydration ring closure to generate intermediate E. The molar ratio of intermediate C to benzamidine hydrochloride is 1:1 to 1.1. The structural formula of benzamidine hydrochloride is R1 is phenyl or biphenyl, and the structural formula of intermediate E is

[0017] Step 3: Intermediate E is selectively oxidized by DDQ oxidant to generate intermediate F, the weight ratio of intermediate E to DDQ oxidant is 1.5-1.7:1, and the structural formula of intermediate F is

[0018] Step 4: Intermediate F and chromium trioxide undergo oxidation reaction to generate intermediate G. The molar ratio of intermediate F to chromium trioxide is 1:2. The structural formula of intermediate G is

[0019] Step 5: The intermediate G and substrate H are dehydrated under reflux of acetic acid to generate product M. The molar ratio of intermediate G to substrate H is 1:1-1.2. The structural formula of substrate H is R3 and R4 are both cycloalkyl groups, and the structural formula of the product M is

[0020]

[0021] Preferably, the step 1 is specifically as follows: weigh substrate A and substrate B into a three-necked flask, then add ethanol, the amount ratio of substrate A to ethanol is 1 mol: 2.5-2.8 L, start stirring, pass argon protection, heat to 60°C-65°C, until the system is basically dissolved, turn off heating, and then add powdered KOH in batches, the molar ratio of substrate A to KOH is 1:2.5, the system has a slight exotherm, and a yellow solid is gradually precipitated. After reacting for 40-45 minutes, the system is heated to reflux and kept warm for 3-5 hours until substrate A reacts completely, and then naturally cooled to room temperature under stirring, and the system is viscous yellow; filter, drain, rinse the solid with ethanol in turn, and drain; then wash and pulp the solid with deionized water for 4-5 times until the pH of the material is <8, and dry the material at 55°C to obtain intermediate C.

[0022] Preferably, step 2 is specifically as follows: weigh the intermediate C and add it to the reaction bottle, then add xylene, the amount ratio of the intermediate C to xylene is 0.1 mol: 0.4-0.5 L, stir evenly, add potassium carbonate after completion, the molar ratio of the intermediate C to potassium carbonate is 1:3.5, the system is turbid, stir for 10 minutes to fully mix, and then add benzamidine hydrochloride twice, stir at room temperature for 15-20 minutes, and then heat the system to reflux for water separation reaction until no more water is discharged from the system and then stop the reaction. The system changes from yellow turbidity to dark brown. The total reaction time is 10-12 hours. After no more water is discharged from the reaction, the xylene in the system is continued to be evaporated, and then the reaction system is cooled to room temperature. A large amount of solids are precipitated in the system, water is added to the system and stirred for 0.5-1h before stopping, filtering, and draining. The solid continues to be eluted with toluene, drained, and then the filter cake is eluted with a large amount of deionized water until it is neutral and then stopped, and placed in a 60°C vacuum dryer to dry to obtain an off-white solid intermediate E.

[0023] Preferably, the step 3 is specifically as follows: weigh the intermediate E into a three-necked flask, add THF, the amount ratio of the intermediate E to THF is 0.1 mol: 550 ml, heat to 40 ° C ~ 50 ° C to dissolve the material, turn off the heating, and then add DDQ in batches, the system quickly turns dark brown, accompanied by temperature rise, the temperature is controlled between 40 ° C ~ 50 ° C, and then the system is slowly heated to 60 ° C ~ 75 ° C for 2 hours of insulation reaction until the reaction is complete; after the reaction is completed, the system is cooled to room temperature, the reaction solution is slowly poured into a sodium bisulfite aqueous solution, stirred thoroughly, and then toluene is added to fully extract, the above-mentioned mixed solution is passed through a diatomaceous earth funnel and the filtrate is collected, the filtrate is continued to be washed with water twice and then concentrated under reduced pressure to a remaining volume of about 100 mL, ethanol is added to fully slurry and disperse the precipitated solid, filtered at room temperature, and drained to obtain a slightly yellow solid intermediate F.

[0024] Preferably, step 4 is specifically as follows: adding intermediate F to a three-necked flask, and then adding chlorobenzene and acetic acid, the amount ratio of intermediate F to chlorobenzene and acetic acid is 0.09 mol: 1L: 200ml, heating to an internal temperature of 70°C to 80°C until the substrate is basically completely dissolved, turning off the heating, and then adding CrO3 in batches. After completion, continue to heat the system to 110°C to 113°C and continue to react for 3h until the reaction is complete; after the reaction solution is cooled to room temperature, water is added, the turbid liquid is passed through a diatomaceous earth funnel, the filter cake is rinsed with toluene, and the filtrate is collected. The filtrate is washed three times with water and then added with anhydrous sodium sulfate to dry. The dried organic phase is passed through a silica gel column, the column liquid is collected, and then concentrated under reduced pressure until the remaining volume is less than 150mL and then stopped. At this time, a large amount of solid has precipitated, and the reaction is filtered after cooling to room temperature, drained, and dried at 60°C to obtain a brown solid intermediate G.

[0025] Preferably, step 5 is specifically as follows: adding intermediate G into a three-necked flask, adding acetic acid, the ratio of intermediate G to acetic acid is 0.075 mol: 400 mL, starting stirring, and then adding substrate H, replacing the system with argon twice, heating the system to reflux and keeping the reaction for 6 to 8 hours until the reaction is complete, and then cooling the system to room temperature, filtering, draining, rinsing with ethanol, draining, and then rinsing with deionized water, and draining to obtain an off-white solid product M.

[0026] Preferably, a phenanthroline derivative is an electron transport material, and the structural formula of the phenanthroline derivative is Wherein R1 is phenyl, R2 is Substituted phenyl, R3, R4 are cyclohexyl, R5 is (1-substituted benzimidazole), (2-substituted quinoline) or (2-substituted benzoxazole).

[0027] Preferably, the structural formula of the phenanthroline derivative is:

[0028]

[0029]

[0030]

[0031] Preferably, an application method of a phenanthroline derivative as an electron transport material, wherein the phenanthroline derivative is used to prepare a test device, wherein the cathode is a magnesium-silver alloy with a volume ratio of 10:1 and a thickness of The anode is ITO glass substrate with a thickness of 100 mm; EML uses Alq3 as the light-emitting layer doped with 0.5% C545T, with a thickness of HTL uses NPB as the hole transport layer with a thickness of The ETL is selected from one or more combinations of compounds 1 to 9 of the above-mentioned electron transport material phenanthroline derivative, and has a thickness of

[0032] Preferably, the preparation process of the test device is: The ITO glass substrate was cut into a size of 30 mm × 30 mm × 1 mm, and was prepared into an experimental substrate with an anode, an anode and an insulating layer using a photolithography process. The surface of the substrate was pretreated with nitrogen and oxygen plasma to increase its surface texture and improve the work function of the anode, and then evaporated on the ITO surface 2-TNATA is used as the hole injection material and then evaporated NPB with a thickness of 1000 NPB is used as the HTL layer material; then Alq30.5% C545T is evaporated as the EML layer with a thickness of Then, one or more combinations of compounds 1 to 9 are evaporated as an ETL layer with a thickness of Then sputter and evaporate on the ETL layer The magnesium-silver alloy is used as the cathode; finally, the multilayer structure is packaged under vacuum to complete the preparation of the test device.

[0033] Compared with the prior art, the advantages of the present invention are:

[0034] (1) The present invention discloses a method for synthesizing a phenanthroline derivative, which is an electron transport material. The phenanthroline compound is further fused and annulated to significantly increase the Tg of the material. The Tg values ​​of compounds 1 to 9 are distributed between 148° C. and 203° C., which are all very high Tg values ​​and fully meet the conventional use temperature requirements. The present invention also increases the large conjugated π bond inside the molecule, effectively improving the electron affinity of the molecule itself. The present invention performs N atom hybridization replacement on the C atom on the phenanthroline, thereby enhancing the electron accepting site of the molecule itself, and making the material have excellent electron binding ability;

[0035] (2) The R2 group of the present invention is preferably adamantane and 1-methylcyclohexane, mainly to adjust the solubility of the material and the consistency of film formation. The R5 group of the present invention is preferably a benzazine heterocyclic substituent group, mainly to increase the electron injection performance of the material, making it easier for the material to obtain electrons from the electron injection layer;

[0036] (3) The present invention selectively and directed oxidizes the intermediate E by selecting different oxidants and oxidation conditions, thereby achieving the smooth introduction of different functional groups;

[0037] (4) The electron migration test results of compounds 1 to 9 of the present invention were distributed in the range of 3.2×10 -5 cm 2 / Vs~6.9×10 -5 cm 2 / Vs,4.8×10 5 V / cm, which has reached the current high level of electron transport materials. Compounds 1 to 9 have higher HOMO energy levels (5.3eV to 6.2eV) and lower LUMO energy levels (2.5eV to 3.3eV), higher energy levels, and better hole blocking ability.

[0038] (5) The raw materials of the present invention are easily available, the conditions of the synthesis process are simple, the preparation process is relatively easy, and it is suitable for large-scale production and preparation. The comprehensive cost performance of the material is high and it is suitable for promotion and use. The electron transport material synthesized by the present invention shows good electron conduction performance on the test device and has potential practical application and promotion value. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 , a schematic diagram of the Tg phase transition temperature of compounds 1 to 9 of the present invention obtained by DSC detection;

[0040] Figure 2 , a schematic structural diagram of the test device of the present invention. DETAILED DESCRIPTION

[0041] The present invention is described below in conjunction with specific examples. The raw materials, solvents and catalysts used are all conventional commercially available products. The following examples are used to illustrate the present invention but are not intended to limit the scope of the present invention.

[0042] The present invention discloses a method for synthesizing a phenanthroline derivative as an electron transport material, comprising the following steps:

[0043] Step 1: Substrate A and substrate B react to generate intermediate C. The molar ratio of substrate A to substrate B is 1:1 to 1.1. The structural formula of substrate A is The structural formula of substrate B is The structural formula of intermediate C is Wherein R2 is a phenyl group substituted with an alkyl group or a cycloalkyl group, and R5 is a fluorine, chlorine, bromine or a benzazaheterocyclic substituent group introduced by reaction;

[0044] Step 2: Intermediate C and benzamidine hydrochloride undergo dehydration ring closure to generate intermediate E. The molar ratio of intermediate C to benzamidine hydrochloride is 1:1 to 1.1. The structural formula of benzamidine hydrochloride is R1 is phenyl or biphenyl, and the structural formula of intermediate E is

[0045] Step 3: Intermediate E is selectively oxidized by DDQ oxidant to generate intermediate F, the weight ratio of intermediate E to DDQ oxidant is 1.5-1.7:1, and the structural formula of intermediate F is

[0046] Step 4: Intermediate F and chromium trioxide undergo oxidation reaction to generate intermediate G. The molar ratio of intermediate F to chromium trioxide is 1:2. The structural formula of intermediate G is

[0047] Step 5: The intermediate G and substrate H are dehydrated under reflux of acetic acid to generate product M. The molar ratio of intermediate G to substrate H is 1:1-1.2. The structural formula of substrate H is R3 and R4 are both cycloalkyl groups, and the structural formula of the product M is

[0048]

[0049] Preferably, the step 1 is specifically as follows: weigh substrate A and substrate B into a three-necked flask, then add ethanol, the amount ratio of substrate A to ethanol is 1 mol: 2.5-2.8 L, start stirring, pass argon protection, heat to 60°C-65°C, until the system is basically dissolved, turn off heating, and then add powdered KOH in batches, the molar ratio of substrate A to KOH is 1:2.5, the system has a slight exotherm, and a yellow solid is gradually precipitated. After reacting for 40-45 minutes, the system is heated to reflux and kept warm for 3-5 hours until substrate A reacts completely, and then naturally cooled to room temperature under stirring, and the system is viscous yellow; filter, drain, rinse the solid with ethanol in turn, and drain; then wash and pulp the solid with deionized water for 4-5 times until the pH of the material is <8, and dry the material at 55°C to obtain intermediate C.

[0050] Preferably, step 2 is specifically as follows: weigh the intermediate C and add it to the reaction bottle, then add xylene, the amount ratio of the intermediate C to xylene is 0.1 mol: 0.4-0.5 L, stir evenly, add potassium carbonate after completion, the molar ratio of the intermediate C to potassium carbonate is 1:3.5, the system is turbid, stir for 10 minutes to fully mix, and then add benzamidine hydrochloride twice, stir at room temperature for 15-20 minutes, and then heat the system to reflux for water separation reaction until no more water is discharged from the system and then stop the reaction. The system changes from yellow turbidity to dark brown. The total reaction time is 10-12 hours. After no more water is discharged from the reaction, the xylene in the system is continued to be evaporated, and then the reaction system is cooled to room temperature. A large amount of solids are precipitated in the system, water is added to the system and stirred for 0.5-1h before stopping, filtering, and draining. The solid continues to be eluted with toluene, drained, and then the filter cake is eluted with a large amount of deionized water until it is neutral and then stopped, and placed in a 60°C vacuum dryer to dry to obtain an off-white solid intermediate E.

[0051] Preferably, the step 3 is specifically as follows: weigh the intermediate E into a three-necked flask, add THF, the amount ratio of the intermediate E to THF is 0.1 mol: 550 ml, heat to 40 ° C ~ 50 ° C to dissolve the material, turn off the heating, and then add DDQ in batches, the system quickly turns dark brown, accompanied by temperature rise, the temperature is controlled between 40 ° C ~ 50 ° C, and then the system is slowly heated to 60 ° C ~ 75 ° C for 2 hours of insulation reaction until the reaction is complete; after the reaction is completed, the system is cooled to room temperature, the reaction solution is slowly poured into a sodium bisulfite aqueous solution, stirred thoroughly, and then toluene is added to fully extract, the above-mentioned mixed solution is passed through a diatomaceous earth funnel and the filtrate is collected, the filtrate is continued to be washed with water twice and then concentrated under reduced pressure to a remaining volume of about 100 mL, ethanol is added to fully slurry and disperse the precipitated solid, filtered at room temperature, and drained to obtain a slightly yellow solid intermediate F.

[0052] Preferably, step 4 is specifically as follows: adding intermediate F to a three-necked flask, and then adding chlorobenzene and acetic acid, the amount ratio of intermediate F to chlorobenzene and acetic acid is 0.09 mol: 1L: 200ml, heating to an internal temperature of 70°C to 80°C until the substrate is basically completely dissolved, turning off the heating, and then adding CrO3 in batches. After completion, continue to heat the system to 110°C to 113°C and continue to react for 3h until the reaction is complete; after the reaction solution is cooled to room temperature, water is added, the turbid liquid is passed through a diatomaceous earth funnel, the filter cake is rinsed with toluene, and the filtrate is collected. The filtrate is washed three times with water and then added with anhydrous sodium sulfate to dry. The dried organic phase is passed through a silica gel column, the column liquid is collected, and then concentrated under reduced pressure until the remaining volume is less than 150mL and then stopped. At this time, a large amount of solid has precipitated, and the reaction is filtered after cooling to room temperature, drained, and dried at 60°C to obtain a brown solid intermediate G.

[0053] Preferably, step 5 is specifically as follows: adding intermediate G into a three-necked flask, adding acetic acid, the ratio of intermediate G to acetic acid is 0.075 mol: 400 mL, starting stirring, and then adding substrate H, replacing the system with argon twice, heating the system to reflux and keeping the reaction for 6 to 8 hours until the reaction is complete, and then cooling the system to room temperature, filtering, draining, rinsing with ethanol, draining, and then rinsing with deionized water, and draining to obtain an off-white solid product M.

[0054] Preferably, a phenanthroline derivative is an electron transport material, and the structural formula of the phenanthroline derivative is Wherein R1 is phenyl, R2 is Substituted phenyl, R3, R4 are cyclohexyl, R5 is

[0055] Preferably, an application method of a phenanthroline derivative as an electron transport material, wherein the phenanthroline derivative is used to prepare a test device, wherein the cathode is a magnesium-silver alloy with a volume ratio of 10:1 and a thickness of The anode is ITO glass substrate with a thickness of 100 mm; EML uses Alq3 as the light-emitting layer doped with 0.5% C545T, with a thickness of HTL uses NPB as the hole transport layer with a thickness of The ETL is selected from one or more combinations of compounds 1 to 9 of the above-mentioned electron transport material phenanthroline derivative, and has a thickness of

[0056] Preferably, the preparation process of the test device is: The ITO glass substrate was cut into a size of 30 mm × 30 mm × 1 mm, and was prepared into an experimental substrate with an anode, an anode and an insulating layer using a photolithography process. The surface of the substrate was pretreated with nitrogen and oxygen plasma to increase its surface texture and improve the work function of the anode, and then evaporated on the ITO surface 2-TNATA is used as the hole injection material and then evaporated NPB with a thickness of 1000 NPB is used as the HTL layer material; then Alq30.5% C545T is evaporated as the EML layer with a thickness of Then, one or more combinations of compounds 1 to 9 are evaporated as an ETL layer with a thickness of Then sputter and evaporate on the ETL layer The magnesium-silver alloy is used as the cathode; finally, the multilayer structure is packaged under vacuum to complete the preparation of the test device.

[0057] The core body of the phenanthroline derivative of the present invention is as follows:

[0058]

[0059] Wherein R1, R2, R3, R4, R5 are corresponding substituent groups;

[0060] R1 is a conventional substituent or derivative of benzene such as phenyl or biphenyl, fluorobenzenes, alkyl-substituted benzenes, and is preferably phenyl.

[0061] R2 is preferably a phenyl group substituted by an alkyl group or a cycloalkyl group, preferably a para-cycloalkyl group; except for a phenyl group substituted by an alkyl group at the 4th position, it can be a 2-substituted alkyl group, or an alkyl group substituted at the 3rd position; the alkyl group can be other alkyl substituents such as methyl, tert-butyl, isopropyl, butyl, etc. except for adamantane and methylcyclohexane.

[0062] R3, R4 are cycloalkyl groups, preferably the same cycloalkyl groups, such as adamantyl, cyclohexyl, 1-methylcyclohexyl;

[0063] R3 and R4 may be the same substituent or different substituents, and may be phenyl or a phenyl derivative, an alkyl derivative or a mixed derivative of phenyl and alkyl.

[0064] R5 is fluorine, chlorine, bromine or a benzazaheterocyclic substituent group introduced by reaction, preferably benzimidazole, quinazoline, benzoxazole, etc. In addition to the preferred azole derivatives, thiazole derivatives, cyanuric chloride derivatives, benzonitrile and other derivatives containing strong negatively charged groups can also be used.

[0065] The preferred compound structural formula is shown below:

[0066]

[0067]

[0068]

[0069] The core main synthesis process route diagram of the diphenanthroline derivatives of the present invention is as follows:

[0070]

[0071] The synthesis process reaction overview is as follows:

[0072] Step 1: Chalcone synthesis process, substrate A and substrate B react to generate intermediate C;

[0073] Step 2: Intermediate C and benzamidine hydrochloride undergo dehydration ring closure to generate intermediate E;

[0074] Step 3: Intermediate E is selectively oxidized to pyrimidine ring intermediate F using DDQ oxidant at 50℃~80℃;

[0075] Step 4: intermediate F is oxidized with chromium trioxide to form methylene to form diketone intermediate G;

[0076] Step 5: Intermediate G and substrate H are refluxed with acetic acid to dehydrate diketone and diamine to form product M.

[0077] The preferred electron transport materials listed in compounds 1 to 9 are described in the following during the synthesis process:

[0078] Example 1: Starting materials of compound 1, compound 2 and compound 3:

[0079] A is 7-bromo-3,4-dihydro-2H-1-naphthalenone;

[0080] B is 4-(1-adamantyl)benzaldehyde;

[0081] D is benzamidine hydrochloride;

[0082] H is (1S,2S)-1,2-dicyclohexylethane-1,2-diamine;

[0083] In the above general formula, R5 refers to a substituent of the preferred material 1 to 9 compound, and can be introduced first or later in the actual synthesis process; this embodiment adopts a later introduction strategy, in which bromine is first used to occupy the position, and then the bromine is replaced by a benzazaheterocyclic substituent group of R5 through a reaction to obtain the target compound, and the R5 side chain is finally introduced through a conventional CC or CN coupling reaction.

[0084] Example 2: Starting materials of compound 4, compound 5 and compound 6:

[0085] A is 7-bromo-3,4-dihydro-2H-1-naphthalenone;

[0086] B is 4-(1-1-methylcyclohexyl)benzaldehyde;

[0087] D is benzamidine hydrochloride;

[0088] H is (1S,2S)-1,2-dicyclohexylethane-1,2-diamine;

[0089] The R5 branch is introduced last via conventional CC or CN coupling reaction.

[0090] Example 3: Starting materials of compound 7, compound 8 and compound 9:

[0091] A is 7-bromo-3,4-dihydro-2H-1-naphthalenone;

[0092] B is 4-(1-1-methylcyclohexyl)benzaldehyde;

[0093] D is benzamidine hydrochloride;

[0094] H is 1,2-diphenylethylenediamine;

[0095] The R5 branch is introduced last via conventional CC or CN coupling reaction.

[0096] The specific synthesis implementation process is described as follows, taking the experimental process of compound 3 as an example:

[0097] Step 1:

[0098] Synthesis of intermediate C: Weigh 225 g (1.0 mol) of 7-bromo-3,4-dihydro-2H-1-naphthalenone and 252 g (1.05 mol) of 4-(1-adamantyl)benzaldehyde into a 5 L three-necked flask, then add 2.7 L of ethanol, start stirring, pass argon protection, raise the temperature to 60°C~65°C until the system is basically dissolved, turn off the heating, and then add 140 g (2.5 mol) of powdered KOH in batches. The system has a slight exotherm and gradually precipitates a yellow solid. After 40 minutes of addition, the system is heated to reflux (75°C~77°C) and kept warm for 3 hours until 7-bromo-3,4-dihydro-2H-1-naphthalenone reacts completely, then naturally cool to room temperature under stirring, and the system is viscous yellow. Filter and drain, rinse the solid with 500 mL of ethanol and drain; then wash and slurry the solid with 3 L of deionized water 4-5 times until the pH of the material is <8, dry the material at 55°C to obtain 389 g of bright yellow solid powder, with a yield of 87%. LC-MS shows a molecular weight of 446.

[0099] Step 2:

[0100] Synthesis of intermediate E: Weigh 112g (0.25mol) of the yellow solid product of the first step, add it to a 2L reaction bottle, then add 1.1L of xylene, stir evenly, add 120g (0.87mol) of potassium carbonate after completion, the system is turbid, stir for 10min to mix well, add 40g (0.27mol) of benzamidine hydrochloride twice, stir at room temperature for 15-20min, heat the system to reflux for water separation reaction, stop the reaction until no more water is discharged from the system, the system changes from yellow turbidity to dark brown, and the total reaction time is about 10-12h. After no more water is discharged from the reaction, continue to evaporate about 600mL of xylene in the system and stop, then cool the reaction system to room temperature, and a large amount of solid precipitates from the system. Add 500 mL of water into the system and stir thoroughly for 0.5 h, then stop, filter, and drain. Continue to rinse the solid with 150 mL of toluene, drain, and then rinse the filter cake with a large amount of deionized water until it is neutral, then stop, place in a vacuum dryer and dry (60°C) to obtain 105 g of an off-white solid with LC purity of 98%, LC-MS molecular weight of 548, and a yield of 76%.

[0101] Step 3:

[0102] Synthesis of intermediate F: Weigh 55g (0.1mol) of the off-white solid product of the second step into a 1L three-necked flask, add 550mL of THF, heat to 40℃~50℃ to dissolve the material, turn off the heating, and then add 34g of DDQ in batches. The system quickly turns dark brown and is accompanied by temperature rise. After the temperature is controlled between 40℃~50℃, the system is slowly heated to 60℃~75℃ and kept warm for 2h until the reaction is complete. After the reaction is completed, the system is cooled to room temperature, and the reaction solution is slowly poured into 1L 0.1mol / L sodium bisulfite aqueous solution. After sufficient stirring, 2.2L of toluene is added to fully extract. The above mixed solution is passed through a diatomaceous earth funnel and the filtrate is collected. The filtrate was washed twice more with 1 L of water each time and then concentrated under reduced pressure until about 100 mL of volume remained. 200 mL of ethanol was added to fully slurry and disperse the precipitated solid. The solid was filtered at room temperature and dried to obtain 50.4 g of a slightly yellow solid with LC purity of 97%, LC-MS molecular weight of 546, and a yield of 92%.

[0103] In addition to DDQ as an oxidant, DCQ and other similar oxidants can also be used to achieve this.

[0104] Step 4:

[0105] Synthesis of intermediate G: Add 50.4 g (0.092 mol) of the third step material into a 2L three-necked flask, then add 1L of chlorobenzene and 200mL of acetic acid, raise the temperature to 70°C ~ 80°C until the substrate is almost completely dissolved, turn off the heating, and then add 18.5 g (0.18 mol) of CrO3 in batches. After completion, continue to heat the system to 110°C ~ 113°C and continue the reaction for 3 hours until the reaction is complete. After the reaction solution was cooled to room temperature, 500 mL of water was added, the turbid solution was passed through a diatomaceous earth funnel, the filter cake was rinsed with 500 mL of toluene, and the filtrate was collected. The filtrate was washed three times with 200 mL of water / time and then dried with anhydrous sodium sulfate. The dried organic phase was passed through a silica gel column, the column liquid was collected, and then concentrated under reduced pressure until the remaining volume was less than 150 mL. At this time, a large amount of solid had precipitated. After cooling to room temperature, it was filtered, drained, and dried at 60°C to obtain 43 g of brown solid with LC purity of 99%, LC-MS molecular weight of 574, and yield of 81%.

[0106] In addition to CrO3, other similar oxidants can also be used as substitutes.

[0107] Step 5:

[0108] Synthesis of product M: Add 43 g (0.075 mol) of the brown solid in the fourth step into a 1L three-necked flask, add 400 mL of acetic acid, start stirring, and then add 17.5 g (0.078 mol) of (1S, 2S)-1,2-dicyclohexylethane-1,2-diamine. After replacing the system with argon twice, heat the system to reflux and keep the reaction for 6 to 8 hours until the reaction is complete. Then cool the system to room temperature, filter, drain, rinse with 50 mL of ethanol, drain, and then rinse with 200 mL of deionized water, drain to obtain an off-white solid, which is dried at 60°C to obtain 47.4 g, with an LC purity of 98%, an LC-MS molecular weight of 760, and a yield of 83%.

[0109] Synthesis of compound 3 (introduction of R5 group): Weigh 40g (0.052mol) of the off-white product of step 5 above into a 500mL three-necked flask, add 7.5g (0.063mol) of benzoxazole, 16.7g (0.079mol) of tripotassium phosphate, 0.7g (0.002mol) of triphenylphosphine, 0.05g (0.002mol) of copper bromide, 0.1g (0.5mmol) of palladium acetate, 400ml of toluene, replace the system with argon, heat the system to reflux, and keep the reaction for 8 to 10h until the reaction is complete. After the reaction is completed, cool the reaction solution to room temperature and filter it. The filter cake is fully rinsed with 200mL of toluene and the filtrate is collected. The filtrate is washed twice with 200L / time of dilute sulfuric acid (0.1mol / L) and then washed four times with 200mL / time of deionized water, and then sodium sulfate is added to dry it. The dried solution was passed through a silica gel column, the column liquid was collected, and the concentration was stopped under reduced pressure when the remaining volume reached 100 mL. A large amount of solid was precipitated, which was filtered and dried to obtain a white solid with a wet weight of 37 g. The crude product was further slurried and dispersed with 200 ml of ethyl acetate and then dried to obtain a white solid powder, which was dried at 60°C in positive air to obtain 32 g, with an LC purity of 99.8%, an LC-MS molecular weight of 799, and a yield of 77%.

[0110] The synthesis process of compounds 1, 2, 4 to 9 is similar to that of compound 3, and will not be described in detail in this application.

[0111] like Figure 1 As shown, the Tg phase transition temperature of compounds 1 to 9 obtained by DSC detection is Figure 1 It can be seen that the Tg value of the preferred compound 6 is the lowest at 142°C, and the highest is compound 7, with a Tg of 203°C.

[0112] The preferred compounds 1 to 9 were detected by cyclic voltammetry, and their corresponding LUMO and HOMO energy levels were calculated. The electron mobility of the corresponding materials measured by the time-of-flight method is shown in Table 1 below:

[0113] Table 1 LUMO, HOMO energy levels and electron mobility data

[0114]

[0115]

[0116] As shown in Table 1, the electron migration test results of compounds 1 to 9 of the present invention are distributed in the range of 3.2×10 -5 cm 2 / Vs~6.9×10 - 5 cm 2 / Vs,4.8×10 5 V / cm, which has reached a relatively high level of current electron transport materials. Compounds 1 to 9 have higher HOMO energy levels (5.3eV to 6.2eV) and lower LUMO energy levels (2.5eV to 3.3eV), higher energy levels, and better hole blocking ability.

[0117] like Figure 2 As shown, the phenanthroline derivative of the present invention is used to prepare the test device, using the most commonly used three-layer sandwich structure, wherein the cathode is a magnesium-silver alloy with a volume ratio of 10:1 and the thickness is controlled at Anode has A glass substrate with a thick ITO layer; EML uses classic Alq3 doped with 0.5% C545T as the light-emitting layer, and HTL uses traditional NPB as the hole transport layer.

[0118] The preparation process of the test device is as follows:

[0119] The thickness is The ITO glass substrate was cut into a size of 30 mm × 30 mm × 1 mm and prepared into an experimental substrate with a cathode, an anode and an insulating layer using a photolithography process. The surface of the substrate was pretreated with nitrogen and oxygen plasma to increase its surface texture and improve the work function of the anode. Then, the ITO surface was evaporated. 2-TNATA is used as the hole injection material and then evaporated NPB with a thickness of 1000 nm was used as the hole transport layer material; Alq30.5% C545T was then evaporated as the light-emitting layer with a thickness of Then, one or more combinations of compounds 1 to 9 are evaporated as an ETL layer with a thickness of Then sputtering evaporation on the electron transport layer The magnesium-silver alloy is used as the cathode; finally, the multilayer structure is packaged under vacuum to complete the preparation of the test device.

[0120] During the test, it was found that the device can be lit up when the driving voltage is as low as 4.8V, and the highest luminous brightness obtained by the test is up to 16500cd / m 2, proving that the prepared electron transport material has a good electron transport function.

[0121] A single any one of 1 to 9 is used as the ETL layer, and a test device is made according to the device preparation method described above. The data listed in Table 2 below are obtained by collecting and summarizing the experimental data: the luminous brightness and the corresponding test voltage data obtained by the corresponding test device. It can be seen from the table that the highest brightness of the test process using Alq3 doped C545T as the luminescent material is over 10000cd / m 2 , proving that the prepared electron transport material plays a significant role in improving the luminescence efficiency.

[0122] Table 2 Luminous brightness and corresponding test voltage data

[0123] Test No. Starting voltage / V Maximum brightness voltage / V Maximum brightness / cd / ㎡ 1 6.4 24.1 13480 2 5.8 22.4 16500 3 6.0 19.7 12870 4 5.6 18.9 14250 5 5.9 17.6 11700 6 6.2 16.3 13900 7 4.8 15.8 12320 8 5.3 12.8 13350 9 5.5 14.3 10870

[0124] The principle of the present invention is as follows:

[0125] The present invention discloses an electron transport material phenanthroline derivative, the core body of the phenanthroline derivative is The core body is subjected to conventional CC or CN coupling reaction to generate preferred compounds 1-9. The present invention first synthesizes chalcone, then performs a dehydration ring-closing process on phenylhydrazine and chalcone, then selectively oxidizes to form a pyrimidine ring with a DDQ oxidant at 50°C to 80°C, then oxidizes the methylene group to form a diketone with chromium trioxide, and finally dehydrates the diketone and diamine to form a pyrazine core body under reflux with acetic acid, and then performs conventional CC or CN coupling reaction to generate preferred compounds 1-9. The present invention further condenses the phenanthroline compound to significantly increase the Tg of the material, increase the large conjugated π bond inside the molecule, effectively improve the electron affinity of the molecule itself, and perform hybridization replacement of the C atom on the phenanthroline with the N atom to enhance the electron accepting site of the molecule itself, so that the material has excellent electron binding ability.

[0126] The R2 group of the present invention is preferably adamantane and 1-methylcyclohexane, mainly for adjusting the solubility of the material and the consistency of film formation. The R5 group of the present invention is preferably a benzyl azoheterocyclic substituent group, mainly for increasing the electron injection performance of the material and making it easier for the material to obtain electrons from the electron injection layer.

[0127] The present invention selectively and directional oxidizes the intermediate E by selecting different oxidants and oxidation conditions, thereby achieving smooth introduction of different functional groups.

[0128] The electron migration test results of compounds 1 to 9 of the present invention are distributed in the range of 3.2×10 -5 cm 2 / Vs~6.9×10 -5 cm 2 / Vs,4.8×10 5V / cm, which has reached a relatively high level of current electron transport materials. Compounds 1 to 9 have higher HOMO energy levels (5.3eV to 6.2eV) and lower LUMO energy levels (2.5eV to 3.3eV), higher energy levels, and better hole blocking ability.

[0129] The raw materials of the invention are easily available, the conditions of the synthesis process are simple, the preparation process is relatively easy, and it is suitable for large-scale production and preparation. The comprehensive cost performance of the material is high and it is suitable for promotion and use. The electronic transmission material synthesized by the invention shows good electronic conduction performance on the test device and has potential practical application and promotion value.

[0130] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.

[0131] Many other changes and modifications may be made without departing from the concept and scope of the present invention.It should be understood that the present invention is not limited to the specific embodiments, and the scope of the present invention is defined by the appended claims.

Claims

1. A method for synthesizing an electron transport material phenanthroline derivative, characterized in that: The following steps are involved: Step 1: Substrate A and substrate B react to generate intermediate C. The molar ratio of substrate A to substrate B is 1:1 to 1.

1. The structural formula of substrate A is The structural formula of substrate B is The structural formula of intermediate C is Where R2 is Substituted phenyl, R5 is Step 2: Intermediate C and benzamidine hydrochloride undergo dehydration ring closure to generate intermediate E. The molar ratio of intermediate C to benzamidine hydrochloride is 1:1 to 1.

1. The structural formula of benzamidine hydrochloride is R1 is phenyl, and the structural formula of intermediate E is Step 3: Intermediate E is selectively oxidized by DDQ oxidant to generate intermediate F. The weight ratio of intermediate E to DDQ oxidant is 1.5-1.7:

1. The structural formula of intermediate F is Step 4: Intermediate F and chromium trioxide undergo oxidation reaction to generate intermediate G. The molar ratio of intermediate F to chromium trioxide is 1:

2. The structural formula of intermediate G is Step 5: The intermediate G and substrate H are dehydrated under reflux of acetic acid to generate product M. The molar ratio of intermediate G to substrate H is 1:1-1.

2. The structural formula of substrate H is R3 and R4 are both cyclohexyl, and the structural formula of the product M is 2. The method for synthesizing a phenanthroline derivative as an electron transport material according to claim 1, characterized in that: The step 1 is specifically as follows: weighing substrate A and substrate B into a three-necked flask, then adding ethanol, the amount ratio of substrate A to ethanol is 1 mol: 2.5-2.8 L, starting stirring, passing argon protection, heating to 60°C-65°C until the system is basically dissolved, turning off heating, and then adding powdered KOH in batches, the molar ratio of substrate A to KOH is 1:2.5, the system has a slight exotherm, and a yellow solid is gradually precipitated, after reacting for 40-45 minutes, the system is heated to reflux and kept for 3-5 hours until substrate A reacts completely, and then naturally cooled to room temperature under stirring, and the system is viscous yellow; filtering, draining, rinsing the solid with ethanol in turn, and draining; then washing and pulping the solid with deionized water for 4-5 times until the pH of the material is less than 8, and drying the material at 55°C to obtain intermediate C.

3. The method for synthesizing a phenanthroline derivative as an electron transport material according to claim 1, characterized in that: The step 2 is specifically as follows: weighing intermediate C and adding it into a reaction bottle, then adding xylene, the amount ratio of intermediate C to xylene is 0.1 mol: 0.4-0.5 L, stirring evenly, adding potassium carbonate after completion, the molar ratio of intermediate C to potassium carbonate is 1:3.5, the system is turbid, stirring for 10 minutes to fully mix, and then adding benzamidine hydrochloride twice, stirring at room temperature for 15-20 minutes, heating the system to reflux for water separation reaction, until no more water is discharged from the system and then stopping the reaction, the system changes from yellow turbidity to dark brown, the total reaction time is 10N12h, after no more water is discharged from the reaction, the xylene in the system is continuously evaporated, and then the reaction system is cooled to room temperature, a large amount of solids precipitate out of the system, water is added to the system and fully stirred for 0.5-1h and then stopped, filtered, drained, the solid is continuously rinsed with toluene, drained, and then the filter cake is rinsed with a large amount of deionized water until it is neutral and then stopped, placed in a 60°C vacuum dryer to dry to obtain an off-white solid intermediate E.

4. The method for synthesizing a phenanthroline derivative as an electron transport material according to claim 1, characterized in that: The step 3 is specifically as follows: weigh the intermediate E into a three-necked flask, add THF, the ratio of the intermediate E to THF is 0.1 mol: 550 ml, heat to 40°C to 50°C to dissolve the material, turn off the heating, and then add DDQ in batches, the system quickly turns dark brown and is accompanied by temperature rise, the temperature is controlled between 40°C and 50°C, and then the system is slowly heated to 60°C to 75°C after the addition is completed, and the reaction is kept warm for 2 hours until the reaction is complete; after the reaction is completed, the system is cooled to room temperature, the reaction solution is slowly poured into a sodium bisulfite aqueous solution, and toluene is added after sufficient stirring to fully extract, the above-mentioned mixed solution is passed through a diatomaceous earth funnel and the filtrate is collected, the filtrate is continuously washed with water twice, and then concentrated under reduced pressure to a remaining volume of about 100 mL, ethanol is added to fully slurry and disperse the precipitated solid, and the solid is filtered at room temperature and dried to obtain a slightly yellow solid intermediate F.

5. The method for synthesizing a phenanthroline derivative as an electron transport material according to claim 1, characterized in that: The step 4 is specifically as follows: adding intermediate F into a three-necked flask, and then adding chlorobenzene and acetic acid, the amount ratio of intermediate F to chlorobenzene and acetic acid is 0.09mol:1L:200ml, heating to an internal temperature of 70°C-80°C until the substrate is basically completely dissolved, turning off the heating, and then adding CrO3 in batches. After completion, continue to heat the system to 110°C-113°C and continue to react for 3h until the reaction is complete; after the reaction solution is cooled to room temperature, water is added, the turbid liquid is passed through a diatomaceous earth funnel, the filter cake is rinsed with toluene, and the filtrate is collected. The filtrate is washed with water three times and then added with anhydrous sodium sulfate to dry, the dried organic phase is passed through a silica gel column, the column liquid is collected, and then concentrated under reduced pressure until the remaining volume is less than 150mL and then stopped. At this time, a large amount of solid has precipitated, and the reaction solution is cooled to room temperature and filtered, drained, and dried at 60°C to obtain a brown solid intermediate G.

6. The method for synthesizing a phenanthroline derivative as an electron transport material according to claim 1, characterized in that: The step 5 is specifically as follows: adding the intermediate G into a three-necked flask, adding acetic acid, the ratio of the intermediate G to the acetic acid being 0.075 mol:400 mL, starting stirring, and then adding the substrate H, replacing the system with argon twice, heating the system to reflux and keeping the reaction for 6 to 8 hours until the reaction is complete, and then cooling the system to room temperature, filtering, draining, rinsing with ethanol, draining, and then rinsing with deionized water, and draining to obtain an off-white solid product M.

7. An electron transport material phenanthroline derivative, characterized in that: The structural formula of phenanthroline derivatives is Wherein R1 is phenyl, R2 is Substituted phenyl, R3, R4 are cyclohexyl, R5 is 8. The electron transport material phenanthroline derivative according to claim 7, characterized in that: The structural formula of the phenanthroline derivative is:

9. An application method of a phenanthroline derivative as an electron transport material, characterized in that: The phenanthroline derivative is used to prepare a test device, wherein the cathode is a magnesium-silver alloy with a volume ratio of 10:1 and a thickness of The anode is ITO glass substrate with a thickness of 100 mm; EML uses Alq3 as the light-emitting layer doped with 0.5% C545T, with a thickness of HTL uses NPB as the hole transport layer with a thickness of The ETL is selected from one or more combinations of compounds 1 to 6 of a phenanthroline derivative as an electron transport material according to claim 8, and has a thickness of 10. The application method of a phenanthroline derivative as an electron transport material according to claim 9, characterized in that: The preparation process of the test device is as follows: The ITO glass substrate was cut into a size of 30 mm × 30 mm × 1 mm, and was prepared into an experimental substrate with an anode, an anode and an insulating layer using a photolithography process. The surface of the substrate was pretreated with nitrogen and oxygen plasma to increase its surface texture and improve the work function of the anode, and then evaporated on the ITO surface 2-TNATA is used as the hole injection material and then evaporated NPB with a thickness of 1000 NPB is used as the HTL layer material; then Alq30.5% C545T is evaporated as the EML layer with a thickness of Then, one or more combinations of compounds 1 to 6 are evaporated as an ETL layer with a thickness of Then sputter and evaporate on the ETL layer The magnesium-silver alloy is used as the cathode; finally, the multilayer structure is packaged under vacuum to complete the preparation of the test device.

Citation Information

Patent Citations

  • Electroluminescent device

    CN101848882A

  • Organic light emitting compound and organic light emitting device comprising the same

    KR1020110043270A